Interfacial water at synthetic and natural lipid bilayers probed by vibrational sum-frequency generation spectroscopy - Cecchet, F. (Biophysical Bulletin, 2020)
Background: At lipid interfaces, water plays a crucial role in carrying biological processes, so that there is a huge interest in unravelling the behaviour of water close to membranes. At charged bio-interfaces, water dipoles form an organized layer. Probing such an interfacial thin layer buried between macroscopic bulk environments is a real challenge. Vibrational sum frequency generation (SFG) spectroscopy is intrinsically specific to interfaces, and has already proven to be an ideal tool to investigate model membranes and their surrounding water. Objectives: The goal of this work is to measure the vibrational SFG response of interfacial water around different model membranes — from easiest synthetic lipids to more complex natural lipids, — in order to use it as diagnostic signal able to distinguish the lipid bilayer interface by its charge properties. Materials and methods: Lipid bilayers made either of synthetic or natural lipids (Avanti Polar Lipids) were physisorbed on CaF2 prisms (Crystran), by using the method of the spontaneous fusion of lipid vesicles, to form so called solid-supported lipid bilayers (SSLBs). The model membranes were investigated by SFG spectroscopy at the solid/water interface. Results: The SFG response was measured between 3600 cm-1 and 2800 cm-1, where OH stretching vibrations of water molecules show-up. The SFG intensity of the OH peak maximum at 3125 cm-1 was recorded during the adsorption of lipid vesicles on the surface, and provided knowledge of the changes of the charge properties of the interface due to the adsorption of the model membranes. The SFG signal indicated that the organization of water was larger at negatively charged than at positively lipid interfaces, and reached the highest value with natural E. сoli сardiolipin layers. Moreover, when the full composition of natural lipids was unknown, the behaviour of the SFG response enabled establishing the charge characteristics of the corresponding lipid interfaces. Conclusion: The SFG response of water enabled estimating average charge behaviour of synthetic and natural lipid bilayers in pure water, thus paving the way to use the SFG signal of water as new diagnostic tool to identify lipid interfaces.